Urban planning and social inequality.: The state position towards informal trades of advanced marginality in the city of Santa Fe (2010-2022). (Desarrollo, Estado y Espacio, 2023)
Since the mid-1990s in Argentina there has been an emergence of informal labor practices linked to the lack of material necessities of a large part of the population produced, among multiple global variables of the production model, by the national economic policies of that period. In a context of critical precariousness, between necessity and inventiveness, a series of tactics for obtaining material resources appeared, involving, first, the displacement to areas of urban centrality and, second, the occupation of public space for their development. At the same time, there is a process of social and urban fragmentation in Latin American cities that tends to push them towards the periphery, contributing to the consolidation of inequalities by affecting the free circulation and occupation of space by the inhabitants of these areas. The weakening or disappearance of bonds exacerbates the situation of deprivation, provoking new cycles of relegation through the encapsulation of the material conditions of life in the territories of origin. The appearance of these trades in the urban network of Santa Fe city has triggered several debates in public opinion, in the media, and in political decision-making. We propose to carry out an overview of the state positions at the municipal level of the Santa Fe territory referring to the practices of cardboard collectors, carts, homeless, valet and window cleaners, contemplating how it affects their development and assessing how it has impacted social and economic inequality.
Keywords: Social inequality; Survival tactics; Socio-urban fragmentation; Public policies